Unveiling Character Education Practices: A Case Study of SMP IT Nur Hasan - Dewi Mariastuti Khasanah; Sigit Haryanto; Djalal Fuadi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study examines the impact of character education programs at SMP IT Nur Hasan on the formation of religious character and student independence. The purpose of this study is to evaluate the effectiveness of programs such as